2019
DOI: 10.1002/aocs.12213
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Oxidation Rate of Oleic Acid Increased Dramatically at 140 °C Studied using Electron Spin Resonance and GC–MS/MS

Abstract: Thermal oxidation of oleic acid at high temperatures was studied using combination of electron spin resonance (ESR) spin-trapping technique and solid phase microextraction (SPME)-Gas chromatography-mass spectrometry-mass spectrometry (GC-MS/MS). Dimethyl pyridine N-oxide (DMPO) was applied as the spin trap. Alkyl, alkoxyl, and oxidized DMPO adducts were identified in the experimental spectra. At 140 C, the alkyl radical adduct was the major component, accounting for 63.89% of the total radical adducts. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In our experiment, this species was not detected, but we identified a species with a H 0.2081 mT. Similarly, other authors , observed during the thermal oxidation of oleic acid a DMPO adduct having a H 0.212 and 0.19921 mT and interpreted this splitting as due to the γ-hydrogen of an oxidized DMPO adduct where the β-hydrogen was lost. Besides the species with a H 0.2081 mT, we observed another species with only three lines.…”
Section: Resultssupporting
confidence: 85%
“…In our experiment, this species was not detected, but we identified a species with a H 0.2081 mT. Similarly, other authors , observed during the thermal oxidation of oleic acid a DMPO adduct having a H 0.212 and 0.19921 mT and interpreted this splitting as due to the γ-hydrogen of an oxidized DMPO adduct where the β-hydrogen was lost. Besides the species with a H 0.2081 mT, we observed another species with only three lines.…”
Section: Resultssupporting
confidence: 85%
“…The intensity of alkyl radical adducts was kept the highest in the detection process. In our former study, the DMPO-oxidized radical adducts were also oxygen-centered radicals, which formed from the β-cleavage of alkoxyl radical adducts . With the comparison of the radical adducts formed in three kinds of vegetable oil, alkoxyl radicals formed in the initial stage.…”
Section: Resultsmentioning
confidence: 86%
“…In our former study, the DMPO-oxidized radical adducts were also oxygen-centered radicals, which formed from the β-cleavage of alkoxyl radical adducts. 27 With the comparison of the radical adducts formed in three kinds of vegetable oil, alkoxyl radicals formed in the initial stage. Then, alkyl radicals formed and accumulated to be the dominating free radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(E)-2-decenal was employed as an aroma marker of oxidation degradation to quantitatively monitor and describe the quality of packaged olive oil [47]. (E)-2-Decenal also formed by oleic acid being degraded at 140 • C affects the flavor of frying [48,49]. It is derived from the thermal reaction of enzymatic hydrolysates of the protein with oxidized lard [50].…”
Section: Omission Experimentsmentioning
confidence: 99%